J Clin Exp Pharmacol 2019
DOI: 10.35248/2161-1459.19.9.263
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Constituents, Safety and Efficacy Study of Thymus schimperi and Thymus serrulatus

Abstract: Background:The genus Thymus is one of the most taxonomically complex genera in the Lamiaceae family and it includes 250-350 taxa (species and varieties). T. serrulatus Hochst. ex Benth and T. schimperi Ronniger are the two species of thymus which are endemic to Ethiopia; locally known as Tosign. According to WHO 2018 report, NCDs (non-communicable disease) are estimated to account for 39% of all deaths in Ethiopia and Infectious diseases also represent a continuous and increasing threat to human health in deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Figure 5(b) depicts the FT-IR spectrum of uncalcined Fe 3 O 4 NPs. The presence of strong and broad absorption band at 3420 cm -1 is caused by the presence of an O-H stretching vibrations of phytochemicals such as Thymol and Carvacrol [40] and was also due to absorbed water by The scanning electron microscope results confirmed that the grain sizes of the NPs were strongly dependent on mixing ratio of iron salts and leaf extract under the same reaction conditions. The SEM images clearly showed microstructural features and diverse morphologies for Fe 3 O 4 nanopowder.…”
Section: Xrdmentioning
confidence: 75%
“…Figure 5(b) depicts the FT-IR spectrum of uncalcined Fe 3 O 4 NPs. The presence of strong and broad absorption band at 3420 cm -1 is caused by the presence of an O-H stretching vibrations of phytochemicals such as Thymol and Carvacrol [40] and was also due to absorbed water by The scanning electron microscope results confirmed that the grain sizes of the NPs were strongly dependent on mixing ratio of iron salts and leaf extract under the same reaction conditions. The SEM images clearly showed microstructural features and diverse morphologies for Fe 3 O 4 nanopowder.…”
Section: Xrdmentioning
confidence: 75%